Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Pengunjung Desa Wisata Kebun Bibit Kediri Pada Masa Pandemi Covid 19 KEPUASAN PENGUNJUNG DESA WISATA KEBUN BIBIT KEDIRI PADA MASA PANDEMI COVID 19 - Rini Astuti; Lina Saptaria (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
Kebun bibit kediri is one of the tourism destinations that offers a variety of attractive tourist objects for visitors from various regions. This study aims to identify the factors that affect the satisfaction of visitors to kebun bibit kediri. This type of research is descriptive quantitative. The population of this research activity was all visitors to kebun bibit kediri tour during the Covid 19 pandemic. The sampling technique was purposive sampling, namely selecting respondents based on certain criteria. The number of research samples were 80 respondents. Methods of data collection using literature study, interviews, documentation, and questionnaires. The research instrument was measured using a Likert scale. Data analysis techniques using factor analysis. . The results showed that based on the factor analysis that had been carried out, it could be grouped. five factors of concern to the manager, namely 1). service quality factor, 2). Emotional factor, 3). Product quality factors, .4). public facilities factor, 5) price factor. but the dominant factor is the service quality factor. By looking at the existing conditions during the covid  19 conditions, it is hoped that the management will increase the factors that can increase the income of kebun bibit kediri.